A Lagrangian Simulation of the Floating-Arm Trebuchet. (1st May 2017) - Constans, Eric
Summary: The floating-arm trebuchet, a modern variation of a medieval weapon, is a popular project for physics and engineering instructors.We develop and analyze a model of this device as an introduction to constrained Lagrangian dynamics.